Lomofungin, a New Antibiotic Produced by Streptomyces lomondensis sp. n - Johnson, Leroy E. (1969)
Lomofungin is a new antimicrobial agent obtained from the culture broth of Streptomyces lomondensis sp. n. UC-5022. Lomofungin is an acidic, olive-yellow, crystalline compound which inhibits, in vitro, a variety of pathogenic fungi, yeasts, and gram-positive and gram-negative bacteria.